La investigación-acción y la autonomía profesional del profesor - Herminia García Ruso (Universidad de La Rioja, 2013)
We will show the outline of the new teacher briefed in the Education Reform and will make a brief study of the curricular perspectives, showing preference for the reconceptualist perspective of the curriculum. In coherence with this perspective, the propasal of a technical-critical model of teacher training will be included. From this perspective teacher training promotes their own research function in which Action-research, will play a first rate role as a research and training strategy, which could be designed, lead and manipulated by thc teachers themselves to improve their teaching.